Constructivism as a Foundation in Developing Physics Teaching Strategies - Zahara, M.Pd, Laxmi; Putu Budi Adnyana; I Gede Astra Wesnawa; I Putu Wisna Ariawan (Kappa Journal, 2024)
The concept of constructivism has emerged as a key pedagogical approach that highlights the active role of students in constructing knowledge. This theory emphasizes learning through social interaction, experimentation, and self directed discovery, with notable contributions from theorists such as Piaget, Vygotsky, Montessori, and Bruner. This study aims to explore the application of constructivism in teaching physics, specifically focusing on the innovation and effectiveness of this approach in improving learning outcomes. A literature study approach was employed to gather and analyze data from academic journals, textbooks, and previous research articles. The study explored various teaching methods influenced by constructivism, including inquiry-based learning, experiments, demonstrations, and problem-solving activities. Data was collected from a range of academic sources that address the integration of constructivist principles into physics education. The analysis involved reviewing the effectiveness of these approaches in enhancing critical thinking, conceptual understanding, and student engagement in learning. The research found that constructivist teaching methods in physics effectively improve critical thinking, student participation, and understanding of key concepts. Innovative teaching strategies based on constructivism, such as interactive and hands-on learning activities, demonstrated significant improvements in student learning outcomes. This study concludes that the principles of constructivism are highly relevant for physics education, with innovative, constructivist-based teaching strategies proving to be interactive, effective, and impactful in enhancing student learning outcomes.